Corporate Social Responsibility, Investment Decisions, and Managerial Ownership on Value of The Company : Evidence from Indonesia - Kenny Ardillah; Thenia Thenia (Ilomata International Journal of Tax and Accounting, 2021)
This study aims to prove the influence of corporate social responsibility, investment decisions and managerial ownership on value of the company. Theories used in this research are agency theory and signal theory. This research was done on all manufacturing companies listed on the Indonesia Stock Exchange for the period of 2016-2018. The sampling method used is purposive sampling technique and the data analysis method used is multiple linear regression analysis. The results of this study show that corporate social responsibility and managerial ownership have no influence on value of the company, while investment decisions have a positive influence on value of the company. Few suggestions for the further research are adjust research periods, use other criteria of sample, use other indicators such as funding decisions, company size, other corporate governance indicators, or use other methods to measure value of the company.